Pengaruh Manajemen Skill terhadap Orientasi Bisnis dan Tingkat Penerimaan Risiko dalam Kewirausahaan dan dampaknya terhaoap Proses Pengembangan Tim, Proses Pengembangan Kualitas, Proses Pengembangan Produk serta Kinerja . Manufaktur Industri Kecil di Jawa Timur - Surachman (2005)
Recently, competitiveness of small industry in East Java has low impact on economic growth and labour supply. Nowadays, the entrepreneurship research that connected with innovation activity and industrial competitiveness is very limited. Therefore, this research examined the effect of entrepreneurship variables to the innovation activities at small industry and their impact on manufacturing performance. This research was carried out in East Java. The population of this research was 591 small industries, which were selected on the basis of proportional area random sampling technique. Out of the population, 115 small firms participated in this study. The data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.3 SOITW ARE. The findings of this research indicated that: (I) the result of mean score value of management skill is high, risk acceptance level is low, and business orientation is moderate; (2) the effect of management skill toward risk acceptance, business orientation, and team development is positive and significant, but it does not directly affect toward quality development, product development, and manufacturing performance; (3) business orientation did not have effect significantly toward product development and manufacturing performance (4) risk acceptance level affects significantly toward quality and product development, but it did not have effect toward manufacturing performance; (5) team development affect significantly toward quality and product development, but it did not have effect toward manufacturing performance, (7) product development affects significantly toward manufacturing performance.